Applying the RE-AIM Model to Asset-Based Community Health Interventions: A Multiple Case Study in Tower Hamlets, London, UK - Kaminska, Karolina (Université d'Ottawa / University of Ottawa, 2016)
Public health policy and practice principally acknowledge a needs-based approach when developing, implementing, and evaluating community health programs. This needs-based perspective receives criticism because it focuses too heavily on what is missing or wrong with communities as opposed to building on their strengths. As a result, community members are perceived as passive recipients, which is disempowering, and ultimately risks creating unsustainable and ineffective programs. In recent years, there has been a growing interest in achieving a balance between the needs-based approach and the asset-based approach, which accentuates positive capabilities. While the amount of literature discussing the benefits of this latter perspective has grown substantially, accompanying evaluation required to sustain continued investment has been limited. Compared to needs-based research, there is less literature on asset-based evaluation. Emphasis on such research could contribute to the progression of evaluation methodologies and theories, ultimately encouraging their use. The purpose of this study is to apply an existing public health evaluation framework – the RE-AIM model (Glasgow, Vogt, and Boles, 1999) – to asset-based community health interventions and to examine the utility of such an evaluation structure across a variety of asset-based health projects. A multiple case study design facilitated comparison of the applicability of the RE-AIM model dimensions – Reach, Effectiveness, Adoption, Implementation, and Maintenance across three cases in the East London borough of Tower Hamlets, United Kingdom. These included the Local Links Asset-mapping project, the Healthy Early Years Project, and the Good Moves project. The RE-AIM framework is additionally guided by principles of the Realist Evaluation approach (Pawson and Tilley, 1997). This research study contributes to asset-based research by providing a guideline and conceptual framework to support asset-based intervention evaluation theory and practice.
Keywords: Community engagement; Evaluation; Asset-based; RE-AIM; health assets; Tower Hamlets; Realist Evaluation; London; United Kingdom; Salutogenesis; Asset Model; Asset-mapping; Multiple Case Study